Tantangan Pondok Pesantren dalam Menghadapi Era Bonus Demografi - Ibnu Chudzaifah (LPPM IAIN Sorong, 2018)
Pondok Pesantren is one of the Islamic educational institutions that aim to form human beings who have noble character, so that created a human who has a balance between physical and spiritual. Some educational institutions offer various models of learning to balance the current development so that its existence is still recognized by the community. While boarding school in dealing with the development of the times, has a commitment to make new innovations by presenting the pattern of education that can give birth to a reliable Human Resources. Especially pesantren currently has a challenging enough weight in facing the era of